What's the Difference? Reflections on Discourses of Morality, Modernism, and Mosaics in the Study of Music in Canada - Diamond, Beverley (Canadian University Music Review / Revue de musique des universités canadiennes, 2000)
In different periods of Canadian cultural history, social difference has been articulated by means of discourses of morality, modernism, or mosaics (among others). Each realm of discourse has negotiated various fields of tension between, for instance, the local and the global, tradition and hybridity, or mediated and live performance. These fields of tension are not easily apparent unless we compare discourses relating to different genres of music and sociomusical spheres. The ways in which Canadian ethnomusicology has been complicit with strategies of "managing difference" become clearer with such analysis. Possible post-colonial strategies for empowering voices of difference are also considered in relation to Canadian studies.